Constructing Multiphase‐Induced Interfacial Polarization to Surpass Defect‐Induced Polarization in Multielement Sulfide Absorbers - Shengchong Hui; Xu Zhou; Limin Zhang; Hongjing Wu (Advanced Science, 2024)
Abstract The extremely weak heterointerface construction of high‐entropy materials (HEM) hinders them being the electromagnetic wave (EMW) absorbers with ideal properties. To address this issue, this study proposes multiphase interfacial engineering and results in a multiphase‐induced interfacial polarization loss in multielement sulfides. Through the selection of atoms with diverse reaction activities, the multiphase interfacial components of CuS (1 0 5), Fe0.5Ni0.5S2 (2 1 0), and CuFe2S3 (2 0 0) are constructed to enhance the interfacial polarization loss in multielement Cu‐based sulfides. Compared with single‐phase high‐entropy Zn‐based sulfides (ZnFeCoNiCr‐S), the multiphase Cu‐based sulfides (CuFeCoNiCr‐S) possess optimized EMW absorption properties (effective absorption bandwidth (EAB) of 6.70 GHz at 2.00 mm) due to the existence of specific interface of CuS (1 0 5)/CuFe2S3 (2 0 0) with proper EM parameters. Furthermore, single‐phase ZnFeCoNiCr‐S into FeNi2S4 (3 1 1)/(Zn, Fe)S (1 1 1) heterointerface through 400 °C heat‐treated is decomposed. The EMW absorption properties are enhanced by strong interfacial polarization (EAB of 4.83 GHz at 1.45 mm). This work reveals the reasons for the limited EMW absorption properties of high‐entropy sulfides and proposes multiphase interface engineering to improve charge accumulation and polarization between specific interfaces, leading to the enhanced EMW absorption properties.